Case report: Acrodermatitis enteropathica result from a novel SLC39A4 gene mutation - Wenjing Hua; Wenjing Hua; Jialin Zou; Yuan Zhuang; Taiguang Zhou (Frontiers Media S.A., 2022)
The clinical data and gene sequencing results in a child with acrodermatitis enteropathica were retrospectively reported, and the related literature was reviewed. A girl aged 9 years and 4 months presented with a repeated skin rash, mainly distributed in the perioral, anogenital, and acral areas, accompanied with alopecia, and a low blood zinc level was found many times. A significant improvement was seen after continuous zinc supplementation. The genetic sequencing test demonstrated that the patient had compound heterozygous for two SLC39A4 mutations: c.1466dupT (p.S490Efs*155) and c.295G > A (p.A99T), and her parents were heterozygous carriers of these two mutations. An improvement was achieved after continuous zinc supplementation. This case report might guide further research on this aspect.